Impact of climate change on monthly streamflow in the Verde River Basin using two hydrological models - Carvalho,Vinícius Siqueira Oliveira (2021)
Abstract This study assessed the impact of climate change on monthly streamflow in the Verde River Basin, located in the Grande River Basin headwater. For this purpose, the SWAT and VIC hydrological models were used to simulate the monthly streamflow under RCP4.5 and RCP8.5 scenarios, obtained by Regional Climate Models Eta-HadGEM2-ES, Eta-CanESM2 and Eta-MIROC5 in the baseline period (1961-2005) and three time-slice (2011-2040, 2041-2070, and 2071-2099) inputs. At the end of the century, the Eta-HadGEM2-ES showed larger decrease of precipitation in both radiative scenarios, with an annual reduction of 17.4 (RCP4.5) and 32.3% (RCP8.5), while the Eta-CanESM2 indicated major warming, with an annual increase of 4.7 and 10.2°C under RCP4.5 and RCP8.5, respectively. As well as precipitation changes, the Eta-HadGEM2-ES also showed greater impacts on streamflow under RCP4.5 for the first time-slice (2011-2040), with an annual decrease of 58.0% for both hydrological models, and for the RCP8.5 scenario by the end the century (2071-2099), with an annual reduction of 54.0 (VIC model) and 56.8% (SWAT model). Regarding monthly streamflow, the Eta-HadGEM2-ES and Eta-CanESM2 inputs indicated decrease under the RCP8.5 scenario by the end the century, varying from 7.2 to 66.3 % (VIC model) and 37.0 to 64.7% (SWAT model). In general, Eta-MIROC5 presented the opposite in terms of direction in the simulations with both hydrological models at the end of the century. Combined effects of climate models, hydrological model structures and scenarios of climate change should be considered in assessments of uncertainties of climate change impacts.